Mostly True Confessions: Joint Meaning-Making about the Thesis Journey - McAlpine, Lynn; Weiss, Joel (Canadian Journal of Higher Education, 2000)
The thesis supervisory role is perhaps the most prominent, yet least understood, of a faculty member's teaching responsibilities. We retrospectively explore the doctoral supervisory experiences of a doctoral student and her thesis supervisor through the process of co-constructing a personal narrative of the journey. Our story addresses several assumptions of the thesis process: the dissertation is an original piece of research by the student; the supervisors in an arms-length relationship because the thesis is the intellectual property of the student; the supervisor and committee are experts while the student is a novice being introduced into the culture; the thesis process is the same regardless of the program and the goals of student and supervisor. We invite others to join our conversation by sharing stories of their experiences. By accumulating knowledge in an under-researched area, it is possible that higher education can improve its record of successfully completed doctoral dissertations.